An audit of a medical anticoagulant clinic in a District General Hospital. Issue 694 (August 1983) - Shafi, M.; Mayberry, J.; Calcraft, B.
Abstract : The working and costs of the anticoagulant clinic at the Royal Gwent Hospital was reviewed over the period July 1980-June 1981. The hospital notes of the patients were reviewed and a questionnaire distributed to each patient. The majority of patients have cardiac valve problems or deep vein thrombosis, the latter sometimes being associated with pulmonary emboli. No major complications were reported during the year, but 9.7% reported rectal bleeding or haematuria. The annual cost of running the clinic is approximately 20, 000 pounds and, if this is representative of Britain as a whole, about 3.75 million pounds is spent annually on anti-coagulation clinics. Several recommendations are made for improving the anticoagulant clinic service, which includes making sure that the doctor at the clinic and the patient are made aware of the reason for anticoagulation, its duration, and possible side effects and interactions with other drugs.